Language Learning Anxiety: a bometric investigation of stress and language learning using wearable devices - MacDonald, William Tait (Rhodes University, Faculty of Humanities, Department of Psychology)
As Sapolsky (2015) notes, stress research has long been characterised by definitional debates that gave rise to a lack of agreement between theorists. An example of this definitional confusion can be seen in the area of Language Learning Anxiety, where there appears to be confusion in the literature over terms such as anxiety and stress. This study investigated the link between stress and language learning using wearable devices measuring heart rate variance, as a means of establishing the feasibility of using this new technology in stress research. The results indicate that the contextualised longitudinal data delivered by wearable devices mitigates against the current dominant paradigm in Language Learning Anxiety, which postulates a straight-line negative correlation between stress and learning. Instead, the inverted U stress relationship proposed by theorists such as Hebb (1955) seem to be a better fit for the data. The nature of the contextualised data generated in this study allowed for comparisons between participants' stress readings in academic contexts, such as language and non-language classes, and their free time. The findings suggest that certain long-held assumptions about heightened stress in academic contexts may not hold true. While the findings of this study did not reach the levels of statistical significance, they constitute proof of concept that the type of contextualised data delivered by wearable devices may allow for a new type of stress research that incorporates contextualising longitudinal perspectives on participants' stress levels. In this study the inclusion of contextualising data led to fundamentally different conclusions about the relationship between stress and language learning. The same may be true of many areas of stress research. The findings presented in this study have broader paradigm-altering implications not only for educational policy, but also for stress research in general. Perhaps equally important was that the type of data delivered by wearable devices was qualitatively different from that normally associated with quantitative studies. This presented challenges in data analysis in this study, but also opens intriguing possibilities regarding a means of reconciling the qualitative and quantitative split in research modalities. The use of wearable devices is not without issues, and some of the issues, ranging from practical considerations to ethical conundrums, are presented for the reader's consideration and to inform future researchers regarding potential pitfalls.
Keywords: Language and languages-- Study and teaching Psychological aspects; Wearable technology; Heart rate monitoring; Stress (Psychology) Testing; Anxiety Testing